A mixed‐methods evaluation of home‐based primary care in dementia within an integrated system. Issue 4 (22nd December 2021) - Nguyen, Huong Q.; Vallejo, Jessica D.; Macias, Mayra; Shiffman, Maricela Garcia; Rosen, Romina; Mowry, Velda; Omotunde, Omotayo; Hong, Benjamin; Liu, In‐Lu Amy; Borson, Soo
Abstract: Background: No prior studies have examined the effects of home‐based primary care (HBPC) in persons living with dementia (PLWD), within an ecosystem of serious illness care in an integrated healthcare system. Our objectives were to compare the characteristics of PLWD receiving HBPC and their hospital utilization and end‐of‐life care, with those of a matched comparison group, and to understand the experiences of family caregivers of PLWD receiving HBPC. Methods: This mixed‐methods study used a retrospective observational cohort design with PLWD receiving HBPC ( n = 287) from 2015 to 2020 and a strata‐matched comparison group ( n = 861), and qualitative phone interviews with 16 HBPC family caregivers in 2020. Inverse probability of treatment weighting propensity score‐adjusted models were used to compare time‐to‐first hospital‐based utilization and, for decedents, home palliative and hospice care and place of death. Care experience was captured through caregiver interviews. Results: Patients receiving HBPC had a similar risk of hospital utilization [adjusted hazard ratio, 1.06 (95% CI: 0.89–1.26), p = 0.51] as a matched non‐HBPC comparison group after a median follow‐up of 199 days. However, HBPC decedents ( n = 159) were more likely to receive home palliative care or hospice [rate ratio, RR: 1.23 (95% CI: 1.07–1.42), p < 0.01] and to die at home [RR: 1.66 (95% CI: 1.35–2.05), p < 0.001] than were non‐HBPC decedents ( n = 423). Caregivers reported that HBPC provided coordinated, continuous, and convenient care that was aligned with families' priorities and goals; however, some expressed unmet needs, especially for help paying for personal care and medical supplies/equipment, and a desire for clearer communication about program operations and more quality oversight for contract services. Conclusions: Although HBPC for PLWD was associated with a similar risk of hospital utilization compared to a matched non‐HBPC comparison group, HBPC resulted in more patient‐centered end‐of‐life care for decedents. Prospective studies of HBPC that further elicit and address unmet needs are warranted.